Effects of Modified Diet on Suppression of Disease Activity of Rheumatoid Arthritis - Ali, M Yakub; Belayaba, Irina; Borisovna, B; Ali, SMK; Khan, AR; Ahmed, Nur; Mazurov, VI (Bangladesh Journal of Nutrition, 2010)
Bangladesh Journal of Nutrition Vol.17 2004 p.51-68